(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
The aim of the present study was to develop tizanidine controlled release matrix. Formulations were designed using central composite method with the help of design expert version 7.0 software. Avicel pH 101 in the range of 14-50% was used as a filler, while HPMC K4M and K100M in the range of 25-55%, Ethylcellulose 10 ST and 10FP in the range of 15 - 45% and Kollidon SR in the range of 25-60% were used as controlled release agents in designing different formulations. Various physical parameters including powder flow for blends and weight variation, thickness, hardness, friability, disintegration time and in-vitro release were tested for tablets. Assay of tablets were also performed as specified in USP 35 NF 32. Physical parameters of both powder blend and compressed tablets such as compressibility index, angle of repose, weight variation, thickness, hardness, friability, disintegration time and assay were evaluated and found to be satisfactory for formulations K4M2, K4M3, K4M9, K100M2, K100M3, K100M9, E10FP2, E10FP9, KSR2, KSR3 & KSR9. In vitro dissolution study was conducted in 900 ml of 0.1N HCl, phosphate buffer pH 4.5 and 6.8 medium using USP Apparatus II. In vitro release profiles indicated that formulations prepared with Ethocel 10 standard were unable to control the release of drug while formulations K4M2, K100M9, E10FP2 & KSR2 having polymer content ranging from 40-55% showed a controlled drug release pattern in the above mentioned medium. Zero-order drug release kinetics was observed for formulations K4M2, K100M9, E10FP2 & KSR2. Similarity test (f 2) results for K4M2, E10FP2 & KSR2 were found to be comparable with reference formulation K100M9. Response Surface plots were also prepared for evaluating the effect of independent variable on the responses. Stability study was performed as per ICH guidelines and the calculated shelf life was 24-30 months for formulation K4M2, K100M9 and E10FP2.